ANALISIS MAKNA SIMBOLIS DALAM KUMPULAN PUISI MALU (AKU) JADI ORANG INDONESIA KARYA TAUFIQ ISMAIL - Arief Kurniawan; Ade Rahima; Sainil Amral (Universitas Batanghari, 2018)
The purposeof this research to identify symbolic meaning in the poem Puisi Malu (Aku) Jadi Orang Indonesia by Taufiq Ismail which refer to the lexical, grammatical, referential, denotative, connotative, words meaning, terms meaning, conceptual meaning, and assosiative meaning. This research is qualitative descriptive. The source of the data is primary and secondary data. The primary data is taken from the collection of poetry Malu Aku Jadi Orang Indonesia (MAJOI), while secondary data is taken from some books and other references which can be used in analyzing the data. The secondary data is taken from the library of FKIP Batanghari University and district library. The data is analyzed by using hermenutics technique, they are; reading the literature based on the structure of the language by translating and or identifying the meaning of the words or the synonym of the words. The result of the research shows that there is lexical meaning in those ten poetry by Taufiq Ismail. So, it can be concluded that the poetry by Taufiq Ismail has some lexical meanings in relation to convention or agreement. Key Words: anayisis, symbolic meaning, poetry